2011
DOI: 10.1021/ja208007w
|View full text |Cite
|
Sign up to set email alerts
|

On the Reactivity of Mononuclear Iron(V)oxo Complexes

Abstract: Ferric tetraamido macrocyclic ligand (TAML)-based catalysts [Fe{C(6)H(4)-1,2-(NCOCMe(2)NCO)(2)CR(2)}(OH(2))]PPh(4) [1; R = Me (a), Et (b)] are oxidized by m-chloroperoxybenzoic acid at -40 °C in acetonitrile containing trace water in two steps to form Fe(V)oxo complexes (2a,b). These uniquely authenticated Fe(V)(O) species comproportionate with the Fe(III) starting materials 1a,b to give μ-oxo-(Fe(IV))(2) dimers. The comproportionation of 1a-2a is faster and that of 1b-2b is slower than the oxidation by 2a,b o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
129
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(139 citation statements)
references
References 27 publications
9
129
1
Order By: Relevance
“…The electron-transfer steps of the oxidation of Met by Fe(VI) may be given as Equations (6)- (8). This reaction scheme is consistent with the observation of Mössbauer spectrum (i.e.…”
Section: Ferratessupporting
confidence: 83%
See 2 more Smart Citations
“…The electron-transfer steps of the oxidation of Met by Fe(VI) may be given as Equations (6)- (8). This reaction scheme is consistent with the observation of Mössbauer spectrum (i.e.…”
Section: Ferratessupporting
confidence: 83%
“…Interestingly, the reaction schemes, given by Equations (4), (5) and Equations (6)- (8), are in agreement with the suggested initial electron transfer steps from the correlation of the rate constants with reduction potentials for the oxidation of Cys and Met by Fe(VI), respectively. [32] …”
Section: Ferratessupporting
confidence: 78%
See 1 more Smart Citation
“…Corma and co-workers found that a chiral Au(III) complex (LAuCl 3 , L: 2,6-bis[(4R)-phenyl-2-oxazolin-2-yl]pyridine) can enantioselectively epoxidize olefins with dioxygen. Isotopic 18 O 2 labelling experiments reveal that 18 O has been incorporated into the epoxide product, indicating that the gold complex can directly activate dioxygen and transfer oxygen to olefin by a non-radical pathway. 19 Upon adding NaOCl to the gold complex, a new band at 460 nm in the UV-vis spectrum and one at 262 cm À1 in the Raman spectrum were assigned to a gold-oxygen vibration by the authors, indicating that a gold oxo or peroxo species has been formed under oxidation conditions.…”
Section: Oxygen Atom Transfer Reactivity Of the Metal Oxo Moietiesmentioning
confidence: 99%
“…Later, the kinetics and mechanism of this transformation were explored in detail in collaboration with Professor Rudi van Eldik, to whom this issue is devoted [14]. Our investigations of the reactivity of Fe V and Fe IV complexes derived from TAMLs, which were performed at -40 °C in MeCN, revealed that both forms oxidize thioanisoles, though Fe V is by several orders of magnitude more reactive than Fe IV [15]. More recently we explored the reactivity of iron(IV) species in aqueous solution towards hexacyanoferrate(II) as an electron donor [16].…”
Section: Introductionmentioning
confidence: 98%